Crafting Excellence: A Strategic Marketing Analysis of Segmentation, Targeting, and Positioning in Jember's Islamic Primary Schools - Abidin, Zainal; Karim, Abdul; Rusmartiningsih, Entin (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
People now increasingly understand the importance of school quality for the future of their generation. As a result, schools with certain advantages become the leading choice, while schools that do not stand out are increasingly abandoned. In response to this phenomenon, school administrators, including Islamic educational institutions in various regions, are trying to show their superiority over other schools. The aim is to meet the community's needs, hopes, and desires and become the first choice for users of its services. This research uses a qualitative approach with a multisite case study method at Al-Furqan Primary School (SD Al-Furqan) Jember, utilizing in-depth interview techniques, participant observation, and document study. Data analysis was carried out simultaneously using data reduction techniques, data presentation, and concluding and tested through credibility, transferability, and confirmability. The research results show that SD Al-Furqan uses market segmentation by considering socio-economic phenomena, religious attitudes, affiliation with Islamic organizations, and community educational orientation. The target market set is upper-middle-class Muslims who want a balance between learning the Koran, Islamic religious education, and academic achievement. By offering a comprehensive education program, SD Al-Furqan strives to meet holistic educational needs and attract the interest of people who prioritize quality education. Masyarakat kini semakin memahami pentingnya kualitas sekolah untuk masa depan generasi mereka. Sebagai hasilnya, sekolah-sekolah dengan keunggulan tertentu menjadi pilihan utama, sedangkan sekolah yang tidak menonjol semakin ditinggalkan. Menyikapi fenomena ini, pengelola sekolah, termasuk lembaga pendidikan Islam di berbagai daerah, berupaya menunjukkan keunggulan mereka dibandingkan sekolah-sekolah lain. Tujuannya adalah untuk memenuhi kebutuhan, harapan, dan keinginan masyarakat, serta menjadi pilihan utama bagi para pengguna jasanya. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus multisitus di SD Al-Furqan Jember, memanfaatkan teknik wawancara mendalam, observasi partisipatif, dan studi dokumen. Analisis data dilakukan secara simultan dengan teknik reduksi data, penyajian data, dan penarikan simpulan, serta diuji melalui kredibilitas, transferabilitas, dan konfirmabilitas. Hasil penelitian menunjukkan bahwa SD Al-Furqan melakukan segmentasi pasar dengan mempertimbangkan fenomena sosial-ekonomi, sikap keagamaan, afiliasi organisasi keislaman, dan orientasi pendidikan masyarakat. Target pasar yang ditetapkan adalah masyarakat muslim kelas menengah-atas yang menginginkan keseimbangan antara pembelajaran Al-Qur’an, pendidikan agama Islam, dan prestasi akademik. Dengan menawarkan program pendidikan komprehensif, SD Al-Furqan berupaya memenuhi kebutuhan pendidikan holistik dan menarik minat masyarakat yang mengutamakan kualitas pendidikan.